The TAPS project. 17: Readmission to hospital for long term psychiatric patients after discharge to the community. Issue 6860 (24th October 1992) - Thornicroft, G.; Gooch, C.; Dayson, D.
Abstract : OBJECTIVE–To identify risk factors which increase the likelihood of readmission for long stay psychiatric patients after discharge from hospital. DESIGN–Follow up for five years of all long stay patients discharged from two large psychiatric hospitals to compare patients readmitted and not readmitted. SETTING–Friern and Claybury Hospitals in north London and their surrounding catchment areas. Most patients were discharged to staffed or unstaffed group homes. SUBJECTS–357 psychiatric patients who had been in hospital for over one year, of whom 118 were "new" long stay and 239 "old" long stay patients. MAIN OUTCOME MEASURES–Readmission to hospital and length of subsequent stay. RESULTS–Of all discharged patients 97 (27%) were readmitted at some time during the follow up period, 57 (16%) in the first year after discharge, and 31 (9%) then remained in hospital for over a year. The best explanatory factors for readmission were: male sex, younger age group, high number of previous admissions, higher levels of symptomatic and social behavioural disturbance, a diagnosis of manic-depressive psychosis, and living in a non-staffed group home. CONCLUSIONS–During the closure of psychiatric hospitals, facilities need to be preserved for acute relapses among long term, and especially younger, discharged patients. Staffed group homes may help prevent relapse and reduce the number of admission beds required.